Eletrodinâmica quâtica escalar via teoria de perturbação causal: um estudo - Beltran Ramirez, Jhosep Victorino [UNESP] (2014)
We will study the scalar quantum electrodynamics (sQED) by using Causal Perturbation Theory (TPC). In tree level we calculate the photon-boson and boson-boson scattering amplitude as well as vacuum polarization